2020
DOI: 10.1101/2020.06.11.147314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

scGRNom: a computational pipeline of integrative multi-omics analyses for predicting cell-type disease genes and regulatory networks

Abstract: Strong phenotype-genotype associations have been reported across brain diseases. However, understanding underlying gene regulatory mechanisms remains challenging, especially at the cellular level. To address this, we integrated the multi-omics data at the cellular resolution of the human brain: cell-type chromatin interactions, epigenomics and single cell transcriptomics, and predicted cell-type gene regulatory networks linking transcription factors, distal regulatory elements and target genes (e.g., excitator… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 149 publications
(230 reference statements)
0
6
0
Order By: Relevance
“…For instance, our mediation analysis indicated that RORA (a nuclear receptor TF) is a mediator for the trans-eGene RNASEL, which encodes mammalian endoribonuclease. Based on single-cell multi-omics data [15], we found that RORA regulates the gene RNASEL specifically in neuronal cell types [15]. As shown in Fig.…”
Section: Cell-type Gene Regulatory Effects Of Trans-eqtls and Mediatorsmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, our mediation analysis indicated that RORA (a nuclear receptor TF) is a mediator for the trans-eGene RNASEL, which encodes mammalian endoribonuclease. Based on single-cell multi-omics data [15], we found that RORA regulates the gene RNASEL specifically in neuronal cell types [15]. As shown in Fig.…”
Section: Cell-type Gene Regulatory Effects Of Trans-eqtls and Mediatorsmentioning
confidence: 92%
“…As a result, we built a mediator-trans-cis-QTL Gene Regulatory Network (GRN) using mediators (TFs) and trans-network (TGs) cis-network results; this regulatory network links SNPs to mediators to the trans-genes that are regulated by them, respectively. Next, we utilized two types of predicted cell-type GRNs from scGRNom [15] for the major brain cell types: excitatory neurons (Ex1, Ex2, Ex3e, Ex4, Ex5, Ex6a, Ex6b, Ex8, and Ex9), inhibitory neurons (In1a, In1b, In1c, In3, In4a, In4b, In6a, In6b, In7, and In8), microglia, and oligodendrocytes. The first predicted GRN type corresponds to cell-type open chromatin regions from scATAC-seq data.…”
Section: Trans-regulatory Network Linking Variants and Regulatory Elements To Genesmentioning
confidence: 99%
“…RUNX1 binds to numerous Mic-specific genes [20]. Coordination between SPI1 and MEF2C plays pivotal roles in Mic enhancer landscapes [21]. Several TF-TF links, like SPI1-RUNX1 in AD Mic and FOXO3-MEF2C and MEF2A-MEF2C in all 4 TF-TF coordination networks, are annotated AD PPI links by the Contextual PPI [18].…”
Section: Prediction and Comparative Analysis Of Cell-type Coordinatio...mentioning
confidence: 99%
“…Lake et al [46] provides data for 4 CNS cell types: ExNs, InNs, Mic, Oligo. This data undergoes preprocessing according to methods outlined in Jin et al [21], which includes removing genes expressed in <100 cells, normalization and scaling via Seurat [78], imputing single-cell expression using the MAGIC algorithm. The final data comprises 15,694 genes across 13,709 ExNs, 6,045 InNs, 317 Microglia, and 2,657 Oligodendrocyte cells.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation